A Novel α2-Globin Gene Mutation: Hb Debao [α31(B12)Arg→Trp; HBA2: c.94A>T]. (2nd January 2017) - Lin, Li; Chen, Biyan; Yi, Shang; Chen, Qiuli; Wei, Hongwei; Li, Guojian; Zheng, Chenguang; Qiu, Xiao-Xia; He, Sheng
Abstract: We report a novel mutation on the α2-globin gene, Hb Debao [α31(B12)Arg→Trp; HBA2 : c.94A>T] detected in a Chinese family. This mutation gives rise to a previously undescribed hemoglobin (Hb) variant that was undetectable by electrophoretic or chromatographic methods. Hb Debao was associated with an α + -thalassemia (α + -thal) deletion [−α 3.7 (rightward)] producing a mild phenotype with significant microcytosis and hypochromia, while the combination of this mutation with an α 0 -thal deletion (−− SEA ) resulting in a severe form of Hb H (β4) disease, which is consistent with a thalassemic phenotype associated with the novel mutation.